A Deterministic Algorithm for Alpha-Numeric Sequence Comparison with Application to Protein Sequence Detection. Issue 3 (September 2015) - Kheniche, A.; Brahimi, N.; Salhi, A.
This paper is an extension of a deterministic algorithm, [1, 2], that was initially designed to measure the rate of similarity between DNA sequences, and any sequences made up with symbols of alphabets of cardinality 4. Here, a modified and extended version to handle sequences of symbols from alphabets of cardinality > 4 is presented. This extension opens up its application area. As a test ground, we search for peptides within a protein database. Computational results on real data and a comparison with BLAST will be discussed.